IDENTIFIKASI UNSUR PADUAN DAN STRUKTUR MIKRO PERPATAHAN BAUT STANDAR ASTM 325 AKIBAT BEBAN PENGETATAN PADA SYSTEM POWER TRAIN BULLDOZER - Hariadi, Hariadi (Rang Teknik Journal, 2020)
The activity research of investigation, identification, chemical laboratory and strength calculation. Manufactured bolt of ASTM 325 standard from grade 8 with the quenched and tempered and hardness value 353 HV or 58,6 HR, maximum tensile strength 167.123 psi and torque wrench until 320 N < 270 N-m from bolt and grade at same. Indication from metallographic from analysis EDAX diagrams Fe minimums, P (9.7 %), Al (13 - 68,8 %), Mg (1 - 3,7 %), Zn (15,7 %), Cl (1,1 %) and Ca of outer thread, the most probable cause failure because have a degradation strength of materials. Its now, tensile strength maximum in area outer diameter of bolt witch tightening load and microstructure of bolt martensite tempered.